Digital Leadership for Organizational Flexibility: Bibliometric Analysis to Identify Research Trends - Iskandar, Iskandar; Sobandi, A.; Santoso, Budi (Eastasouth Institute, 2024)
In the dynamic and technologically driven era of Society 5.0, digital leadership emerges as a pivotal force in steering organizational flexibility and success. This paper employs a bibliometric analysis to elucidate the evolution and trends in digital leadership research. By analyzing 338 articles from the Scopus database, focusing on 'digital leadership', we reveal significant insights into how digital transformation and leadership agility interplay to enhance organizational outcomes. Our study highlights the indispensable role of digital leadership in fostering innovation, driving sustainable business practices, and navigating the complexities of modern organizational environments. The findings underscore the necessity for leaders to adapt to digital paradigms and cultivate capabilities that align with the rapid changes in technology and society. This research not only maps the current landscape but also provides a valuable reference for practitioners and researchers interested in the intersection of leadership and digital transformation.